Effect of 6 months of whole body vibration on lumbar spine bone density in postmenopausal women: a randomized controlled trial [Corrigendum] - Lai CL (Dove Medical Press, 2014)
Lai CL, Tseng SY, Chen CN, et al. Clin Interv Aging. 2013;8:1603–1609. On page 1603, the author affiliations have been listed incorrectly. The correct author list is as follows:Chung-Liang Lai1,2,6Shiuan-Yu Tseng1,2Chung-Nan Chen3Wan-Chun Liao2Chun-Hou Wang4Meng-Chih Lee1,5,*Pi-Shan Hsu5,*1Institute of Medicine, Chung Shan Medical University, Taichung, Taiwan; 2Department of Physical Medicine and Rehabilitation, Taichung Hospital, Ministry of Health and Welfare, Taichung, Taiwan; 3Department of Radiology, Taichung Hospital, Ministry of Health and Welfare, Taichung, Taiwan; 4School of Physical Therapy, Chung Shan Medical University, Taichung, Taiwan; 5Department of Family Medicine, Taichung Hospital, Ministry of Health and Welfare, Taichung, Taiwan; 6Central Taiwan University of Science and Technology, Taichung, TaiwanRead the original paper